Effect of Germinated Sorghum Flour on the Performance of Laying Hens (Warren) - Bohoua, Guichard L.; Yelakan, Clarisse K. Kone (International Journal of Poultry Science, 2007)
The experiment was conducted using laying hens. They were divided into four groups of eighty two (group I, group II, group III, group IV). They received respectively the basic feeding, and basic feedings supplemented with 0.8%, 1.2%, 1.6% germinated sorghum flour. Data were collected and laying hens weight, egg weight and the feeding efficiency index were calculated. The laying rate was also determined. Group II with 0.8% germinated sorghum had the best result in terms of laying hen weight, the laying rate and the feeding efficiency index. This group is followed by group I, group III, group IV. However, the supplementation had a detrimental effect on the egg weight.